Deviant Behavior of Teenagers in Using Social Media at Ternate City - Bailussy, Wahyuni; Kahar, Suyatno (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
Communication and information problems that occur in today's digital era, have a major influence on its users; There's no denying that technology can make someone unknown famous, and vice versa. Especially for teenagers, social media has a significant impact. According to research by Septian Wulan, in Indonesia, adolescents aged 15-19 years are the largest internet users, reaching 64%. Fenomene The deviant behavior that grabs the attention of the people of Ternate is the behavior of inhaling glue inside the Oranje fortress which is a historical location for this kieraha earth. This glue inhalation behavior for teenagers was reported by several online media, one of which was SuaraTernate.com with the headline